STUDENTS PERCEPTION ON THE USE OF GOOGLE CLASSROOM IN ESSAY WRITING CLASS - Deiniatur, Much (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
The utilization of modern technologies in classrooms such as web-based learning allows learners to learn faster with better function and with more satisfaction from their class attendance. The study aims at investigating the students’ perceptions on the use of Google Classroom in essay writing class of one college in Indonesia. This research was a survey study. The participant of this research was 48 students enrolled in writing class. They were asked to fill out an online survey through Google Forms at the end of the course to investigate their perceptions on the use of Google Classroom. The result showed that students have positive perceptions of the use of Google Classroom in an essay writing class. The students found the activities applied in the Google Classroom help them to write better because the teacher can give feedback to the students’ writing effectively. Furthermore, the use of Google Classroom makes the students ready for autonomous learning. Future study is expected to conduct research and development on the content of the material used for Google Classroom.